Linking peacebuilding, nutrition, and emission reductions - Castro-Nunez, Augusto (2025)
EPINER seeks to develop resilient, low-emission food systems by integrating peace-building strategies for long-term sustainable development. Led by the Bioversity International Alliance and the International Center for Tropical Agriculture, in partnership with the Government of Ireland.